The soft Jacobson radical of a commutative ring - Ghosh, Jayanta; Mandal, Dhananjoy; Samanta, Tapas Kumar (Armenian Journal of Mathematics, 2021)
In this paper, the notion of the soft Jacobson radical of a ring is defined. A relationship between the soft Jacobson radical of a ring and Jacobson semisimple ring is established. Some properties of this notion have been studied under homomorphism.
Keywords: Jacobson radical; Jacobson semisimple ring; soft maximal int-ideal; Soft Jacobson radical